2013
DOI: 10.1021/la400313a
|View full text |Cite
|
Sign up to set email alerts
|

Free Energy and Electronic Properties of Water Adsorption on the SnO2(110) Surface

Abstract: A molecular understanding of the adsorption of water on SnO2 surfaces is crucial for several applications of this metal oxide, including catalysis and gas sensing. We have investigated water adsorption on the SnO2(110) surface using a combination of dynamic and static calculations to gain fundamental insight into the reaction mechanism at room temperature. The reaction dynamics are studied by following water adsorption and dissociation on the SnO2 surface with metadynamics calculations at low and high coverage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
40
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(43 citation statements)
references
References 67 publications
3
40
0
Order By: Relevance
“…In the case of defective (101) and (110) surfaces, the molecular adsorption is enhanced above a vacancy thanks to shorter H-bonds that can be formed between the water molecule and the O O atoms placed in close vicinity 34,43 . Noteworthy, we observed a molecular adsorption (Fig.…”
Section: Defective Surface 20mentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of defective (101) and (110) surfaces, the molecular adsorption is enhanced above a vacancy thanks to shorter H-bonds that can be formed between the water molecule and the O O atoms placed in close vicinity 34,43 . Noteworthy, we observed a molecular adsorption (Fig.…”
Section: Defective Surface 20mentioning
confidence: 99%
“…) because of the formation of a H-bond between the dissociated H atom coming from the water molecule and the dissociated OH adsorbed on Sn atom (d(H bond)= 1.79 Å)34,35,43,44 . Here the two bonds between Sn-Oo are slightly enlarged, from 2.00 Å to 2.16 Å but not broken.…”
mentioning
confidence: 99%
“…OTS molecules are more reactive with –OH groups on the metal oxide surfaces [3133]. Molecular dynamics simulations revealed that the O B site of SnO 2 was the most preferable site for the formation of –OH groups [3435]. Thus, OTS binds dominantly at O B sites over the O P sites of SnO 2 NPs.…”
Section: Resultsmentioning
confidence: 99%
“…8). DFT calculations using the generalized gradient approximation (GGA) indicated that the luminescence transitions around 2 and 2.4 eV belonged to bridging and in-plane oxygen vacancies, respectively [3435 3738]. Similarly Liu et al [37] demonstrated that the in-plane oxygen vacancies were responsible for the creation of shallow donor states while the bridging oxygen vacancies were related to relatively deeper donor states.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, other authors have reported that for the (110) surface, reduced conditions will benefit dissociative behavior. 28 This is because upon exposure to water molecules, the reduced state is first oxidized. This scenario suggests that reduced states would have higher heats of adsorption as the energy for oxidation is exothermic, and contrasts with the data we have acquired.…”
Section: B Heats Of Water Adsorptionmentioning
confidence: 99%